Probable Imprints of Neotectonics or Recent Crustal Movements in Bansloi River Basin, Rajmahal Volcanic Province, Jharkhand, India - Bhattacharji, Manjari (National Geographical Journal of India, 2022)
The probable imprints of neotectonics on the shape and drainage characteristics of the Bansloi river basin, located in the southern portion of the Rajmahal hills, is the subject matter of enquiry in this article. The asymmetric cross section and the series of prominent convexity and concavity of the main and tributary basins have been attributed to the dynamics of regional tectonics (specifically the evolution of Himalayas to its north) on the river systems of the area. The formation of a centripetal drainage site at the lowest reach of the Bansloi due to its sudden northerly turn despite the eastward dip and topographic tilt of the area is another imprint of the neotectonic movement in the area. The sudden northerly turn of the Bansloi appears to have captured the lowest reach of the Torai river, the only left bank tributary of Bansloi, thereby lending a tributary status to this erstwhile independent main river